The Effects of STEAM-Based Activities Gifted Students’ STEAM Attitudes, Cooperative Working Skills and Career Choices - Özge Ceylan Konkuş; Ünsal Umdu Topsakal (Journal of Science Learning, 2022)
STEAM is one of the teaching strategies frequently used in science education in recent years to ensure the development of students of different ages and characteristics. This study aimed to reveal the effect of STEAM-based activities on gifted students' STEAM attitudes, cooperative working skills, and career choices. For this purpose, a single group pre-test post-test design was used. Thirty-seven secondary school fifth-grade students (10-11 years old) diagnosed as gifted participated in the research. STEAM-based activities were applied to the students for ten weeks. STEAM Attitude Scale, Cooperative Learning Process Scale, and an open-ended question form for career choices were used as data collection tools. The Wilcoxon Signed Rank Test was used for the quantitative data analysis, and thematic analysis was used for qualitative data. At the end of the application, it was observed that the students' attitudes toward STEAM increased; cooperative working skills improved; they turned to STEAM disciplines in their career choices. It is recommended to give STEAM education to gifted students from an early and guide them to shape their careers.